Geriatric Syndromes: Clinical, Research, and Policy Implications of a Core Geriatric Concept - Inouye, Sharon K.; Studenski, Stephanie; Tinetti, Mary E.; Kuchel, George A. (Journal of the American Geriatrics Society (JAGS), 2007)
Geriatricians have embraced the term “geriatric syndrome,” using it extensively to highlight the unique features of common health conditions in older people. Geriatric syndromes, such as delirium, falls, incontinence, and frailty, are highly prevalent, multifactorial, and associated with substantial morbidity and poor outcomes. Nevertheless, this central geriatric concept has remained poorly defined. This article reviews criteria for defining geriatric syndromes and proposes a balanced approach of developing preliminary criteria based on peer‐reviewed evidence. Based on a review of the literature, four shared risk factors—older age, baseline cognitive impairment, baseline functional impairment, and impaired mobility—were identified across five common geriatric syndromes (pressure ulcers, incontinence, falls, functional decline, and delirium). Understanding basic mechanisms involved in geriatric syndromes will be critical to advancing research and developing targeted therapeutic options, although given the complexity of these multifactorial conditions, attempts to define relevant mechanisms will need to incorporate more‐complex models, including a focus on synergistic interactions between different risk factors. Finally, major barriers have been identified in translating research advances, such as preventive strategies of proven effectiveness for delirium and falls, into clinical practice and policy initiatives. National strategic initiatives are required to overcome barriers and to achieve clinical, research, and policy advances that will improve quality of life for older persons.